Analysis of Positive Politeness Strategies In Wish Movie - Ni Luh Putri Ayu Febriani; Ni Wayan Sukarini; Ni Luh Sutjiati Beratha (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This undergraduate thesis is aimed to analyze the positive politeness strategies of the characters in the “Wish” movie. The collected data of this undergraduate thesis was analyzed based on the politeness theory by Brown and Levinson (1987). The method used in this undergraduate thesis was descriptive qualitative method. The results of this undergraduate thesis indicate that twelve positive politeness strategies were identified in the conversations of the characters in the